FRI0085 RETENTION RATE OF ADALIMUMAB AND ABP 501 IN THE TREATMENT OF A LARGE COHORT OF PATIENTS WITH INFLAMMATORY ARTHRITIS: A REAL LIFE RETROSPECTIVE ANALYSIS. (2nd June 2020) - Becciolini, A.; Caccavale, R.; Parisi, S.; Giordano, S.; Bravi, E.; DI Donato, E.; Lumetti, F.; Andracco, R.; Ditto, M. C.; Santilli, D.; Lucchini, G.; Volpe, A.; et al.
Abstract : Background: The recent introduction of ABP 501, an adalimumab biosimilar, in treatment of rheumatic diseases was supported by a comprehensive comparability exercise with its originator. On the other hand observational studies comparing adalimumab and ABP 501 in inflammatory arthritis are still lacking. Objectives: To compare the clinical outcomes of the treatment with adalimumab, both originator and biosimilar, in a large cohort of patients affected by autoimmune arthritis in a real life setting. Methods: We retrospectively analysed the baseline characteristics and the retention rate in a cohort of patients who received at least a course of adalimumab (originator or biosimilar ABP 501) in eight Rheumatology Units from January 2003 to January 2020. We stratified the study population according to biosimilar use. Descriptive data are presented by medians (interquartile range [IQR]) for continuous data or as numbers (percentages) for categorical data. Drug survival distribution curves were computed by the Kaplan-Meier method and compared by a stratified log-rank test. P values ≤0.05 were considered statistically significant. Results: 764 patients (53.4% female, median age 55 [44-65] years, median disease duration 60 [25-149] months) treated with adalimumab were included in the analysis. 308 (40.3%) were affect by rheumatoid arthritis, 244 (31.9%) by psoriatic arthritis, and 212 (27.7%) by axial spondylarthritis. 558 (73%) were treated with adalimumab originator and 206 (27%) with ABP 501. Among the biosimilars 60 (29.1%) patients were naïve to adalimumab treatment. The overall 6-month retentions rate was 93.1%. The 6-month retention rate for adalimumab and ABP 501 were 93.3% and 91.2% respectively, without significant differences between the groups (p=0.541). Patients switching from originator to biosimilar showed and overall higher treatment survival when compared to naive (6-month retention rate 95% vs 90-4%), although it was not significant (p=0.179). Conclusion: In our retrospective study adalimumab originator and its biosimilar ABP 501 showed the same effectiveness. Patients switching from originator to biosimilar showed an higher retention rate when compared to naive. Disclosure of Interests: Andrea Becciolini Speakers bureau: Sanofi-Genzyme, UCB and AbbVie, rosalba caccavale: None declared, Simone Parisi: None declared, Salvatore Giordano: None declared, Elena Bravi: None declared, eleonora Di Donato: None declared, Federica Lumetti: None declared, Romina Andracco: None declared, Maria Chiara Ditto: None declared, Daniele Santilli: None declared, Gianluca Lucchini: None declared, Alessandro Volpe: None declared, Antonio Marchetta: None declared, Flavio Mozzani: None declared, Gilda Sandri: None declared, Francesco Girelli: None declared, eugenio arrigoni: None declared, Enrico Fusaro: None declared, marino paroli: None declared, Alarico Ariani: None declared